Ecoenzym quality and potential of residues as bioactivator for organic waste composting - Munif Said Hassan; Abdul Hayat Kasim; Santosa, Slamet (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Ecoenzyme is a complex organic solution that can be an alternative for environmental management. Ecoenzym is made by fermenting water spinach, chinese cabbage, mango, papaya, with palm sugar or granulated sugar and water in plastic bottles of 1500mL for 3 months. Ecoenzyme solution was analyzed for aroma quality, color, pH, volume and alcohol content. Ecoenzyme residues (BRE), effective microorganisms (BEM) and without bioactivator (TBP) were tested for the ability to decompose organic waste aerobically in plastic buckets. All treatments produced an ecoenzyme solution with a strong acid aroma, light brown to reddish brown in color, pH ranging from 3.1-.3.4, volume ranging from 740-780mL and contained alcohol ranging fom 4.1-4.8%. The lowest volume of ecoenzyme solution was 740mL in ECO2 and the highest was 780mL in ECO6. The lowest alcohol content is 4.1% in ECO3 and the highest is 4.8% in ECO5. Residual ecoenzymes (BRE), effective microorganisms (BEM) and without bioactivator (TBP) are able to decompose organic waste with the results of pH, temperature, humidity, total N, P2O5 and K2O that meet the Indonesian national standard (SNI) for composting. The composting pH value ranging from 6.4-7.5, temperature ranging from 27-36oC, humidity ranging from 66-81%, total N ranging from 0.68-0.80%, P2O5 ranging fom 0.49-0.54%, and K2O ranging from 0.75-.0.90%. This study concludes that the use of mango and papaya waste and palm sugar produces an ecoenzyme solution with the highest alcohol content and potential ecoenzyme residues as a bioactivator for organic waste composting